Two-Tiers Test Berbasis Everyday Life Activity Stimulus untuk Meningkatkan Kemampuan Numerasi AKM Siswa Sekolah Dasar - Hapsari, Wilis Putri; Labib, Umar Abdul (Jurnal Didaktika Pendidikan Dasar, 2025)
This research investigated the effectiveness of numeracy assessment with two-tier model and daily life activity stimulus instruments in improving numeracy outcomes. The numeracy instruments were administered to 442 elementary school students in Kulon Progo Regency using random sampling techniques. Instrument validity was established using Aiken’s formula for content validity and Exploratory Factor Analysis (EFA) for construct validity. Reliability was determined using Cronbach’s Alpha. Test quality was analyzed using Item Response Theory (IRT) through Partial Credit Model (PCM) and descriptive analysis to compare the differences in AKM results between 2022 and 2023. The findings indicated that the instrument met the content validity criteria with an Aiken’s index exceeding 0.7 and a KMO-MSA value of 0.78 for construct validity, along with a significant Bartlett’s value of 0.00, confirming construct validity. Reliability was categorized as highly reliable with a Cronbach’s Alpha of 0.872. The instrument could measure student ability within a range of -1.2 to 2.8, providing a maximum information function of 58 and a standard error of 0.7. Numeracy achievement showed an increase of 16.01% compared from years before (30.60%) to the years after (46,67%) the test was held. Therefore, it can be concluded that the two-tier based daily life activity stimulus numeracy assessment instrument possesses good quality and can effectively enhance numeracy achievement.